Sumoylation : molecular biology and biochemistry - Wilson, Van Gene (Horizon Bioscience, 2004)
The Horizon Scientific Press titles focus on high-level microbiology and molecular biology topics. Written by internationally renowned and highly respected leaders in the field, titles in this series comprise of review manuals, practical manuals, and reference texts for research scientists, bioscience professionals and graduate students.Sumoylation is a novel posttranslational modification system, biochemically analogous to, but functionally distinct from, ubiquitinylation. Sumoylation involves the covalent attachment of a SUMO (small ubiquitin-related modifier) to substrate proteins. This modification system has crucial roles in many different biological processes, including protein localization and stability, transcriptional activities, nucleocytoplamic signalling and transport, and genome replication, as well as the regulation of gene expression.The molecular and biochemical mechanisms involved in sumoylation have been the subject of intense interest in recent years. This volume, edited and written by leading international experts, is the first book to be devoted to sumoylation. It presents information on the history, evolution and mechanisms of sumoylation, discusses SUMO proteases, ligases and conjugation pathways, and reviews the impact on modification and nucleocytoplasmic transport, PML nuclear bodies, and transcriptional regulation. In addition, specialist chapters cover the role of sumoylation in yeast, viruses and the tumor suppressor P53.This comprehensive book is the definitive reference volume on all aspects of sumoylation. It is an essential reference manual for all researchers in this area.
Keywords: Protein Processing, Post-Translational; proteiny; Proteins; posttranslační úpravy proteinů; Small Ubiquitin-Related Modifier Proteins; biochemie; malé modifikační proteiny související s ubikvitinem